NATIVE ENGLISH SPEAKING TEACHERS (NESTs) AND INDONESIAN ENGLISH TEACHERS (IETs) EFL STUDENTS’ PERCEPTION AND PREFERENCES - Pariyanto Pariyanto (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
This paper explores EFL students’ perception of Indonesian English Teachers (IETs)/ Non-Native English Speaking Teachers (NNESTs) and Native English Speaking Teachers (NESTs) in English Language Teaching (ELT) in Indonesia. 32 Indonesian EFL university students participated in this study. Employing a five-point Likert scale questionnaire (1= strongly disagree, 2= disagree, 3= neutral, 4= agree, 5= strongly agree) distributed to participants, this study found that (1) students perceived IETs/NNESTs to be better in teaching beginning learners as IETs/NNESTs apply Indonesian into English instruction, sharing the same first language and the same culture, understanding students’ problem in learning English, understanding the questions and providing clear answers, and sharing the same language learning process; (2) students perceived NESTs to be better in teaching advanced learners of English as NESTs are superior in their English proficiency. NESTs are perceived to better in teaching speaking, pronunciation, listening, and culture. This study implies that both IETs/NNSTs and NESTs have their strengths and weaknesses in the English language teaching context.